The Effect of Wearing White Coats on Patients' Appreciation of Physician Communication during Postpartum Rounds: A Randomized Controlled Trial - La Rosa, Mauricio; Spencer, Nicholas; Abdelwahab, Mahmoud; Zambrano, Gabriela; Saoud, Fawzi; Jelliffe, Katherine; Olson, Gayle; Munn, Mary; Saade, George R.; Costantine, Maged (American Journal of Perinatology, 2019)
Objective Wearing a white coat (WC) has been associated with risk of colonization and transmission of resistant pathogens. Also, studies have shown that physicians' attire in general affects patients' confidence in their physician and the patient–physician relationship. Our objective is to evaluate the hypothesis that not wearing a WC during physician postpartum rounds does not affect patient–physician communication scores.Materials and Methods This is an unblinded, randomized, parallel arms, controlled trial of postpartum women at a single university hospital. Women were randomly assigned to having their postpartum physicians' team wear a WC or not (no-WC) during rounds. Our primary outcome was “patient–physician communication” score. Univariable and multivariable analysis were used where appropriate.Results One hundred and seventy-eight patients were enrolled (87 in WC and 91 in no-WC groups). Note that 40.4% of patients did not remember whether the physicians wore a WC or not. There was no difference in the primary outcome (p = 0.64) even after adjusting for possible confounders.Conclusion Not wearing a WC during postpartum rounds did not affect the patient–physician communication or patient satisfaction scores. In the setting of prior reports showing a risk of WC pathogen transmission between patients, our findings cannot support the routine wearing of WCs during postpartum rounds.
Keywords: patient–physician communication scores; patient satisfaction; white coat; attire; postpartum